Recent Seismic Activity in the Azores Region - Borges, J.F. (2008)
This seismic activity in the Azores Region is characterized by sequences of low-magnitude events, usually with epicenter off-shore. These seismic sequences are sometimes triggered by larger events, felt by the population, that could produce significant material and human losses. This characteristic is confirmed by the historical and instrumental seismicity, in particular by the recent earthquakes occurred on 1980 (Mw=6.8), 1997 (Mw=6.2), 1998 (Mw=6.2) and 2007 (Mw=6.3, Mw=6.1). The mechanism responsible for this spatial and temporal seismic pattern still yet not very well known. In this work we discuss the recent (2007) seismic activity of the Azores region by analyzing the spatial and temporal distribution of seismic events associated with two sequences with different characteristics. The fisrt one is a seismic swarm started on April 21st 2007, centered at about 40 kilometers west of the Faial Island (maximum magnitude mb=4.0). The second one corresponds to an aftershock sequence associated to the events of 2007/04/05 (Mw=6.3) and 2007/04/07 (Mw=6.1), both with epicenter in the Formigas Islets and felt (I=V/VI in Mercali scale) in S. Miguel. We calculate the static Coulomb stress change for both events using focal mechanisms derived from the inversion of body waves. We find that the static stress change caused by the April 5 event is higher, about 2 bar at the location of the second event (April 7), triggering the second rupture. Locations of aftershocks do not agree well with areas of increased Coulomb failure stress.